Case Series Coexistence of PFO with Other Conditions - Who’s the Culprit? - Hudaja, Dessytha Nathania; Soetjipto, Aurea Stella; Ariyani, Queen Sugih; Soesanto, Michael; Pardede, Ingrid Maria (The Indonesian Heart Association, 2021)
Background: Patent foramen ovale (PFO) is a major cause of cryptogenic stroke (CS). However, it is still possible that PFO comes with those other conditions during evaluation. This paper presents a series of CS cases highly suspected due to PFO origin with each of its special presentations. Case illustration/summary of a review article: We present three cases of CS with PFO as a possible contributing factor. Case 1 showed a patient with repeated ischemic strokes that was investigated to be cryptogenic in origin. Case 2 showed CS with PFO and occult atrial fibrillation. Case 3 showed CS at a young age caused by a PFO with protein C/S deficiency. Conclusion: The role of PFO as a culprit, risk factor, or a coincidental finding in CS is still debatable and is a controversial issue. Determining PFO as a cause of CS requires a thorough consideration of clinical and PFO anatomical/morphological factors.